Respiratory rates of Eugenia brasiliensis Lam. (Myrtaceae) seeds at modified atmospheres - Cécel, Aline Testoni (2021)
Successful seed conservation depends on reducing the metabolism of both the seeds and other associated organisms. The metabolic activity can be analyzed by the respiratory rates but it depends on the developing of methodological protocols. In addition, modified atmosphere has shown some control in respiration when O2 and CO2 concentrations are changed. This work evaluated the effect of changes in O2 and CO2 concentrations on the inhibition of the respiratory metabolism of Eugenia brasiliensis Lam seeds. The results showed that in atmospheres with CO2 concentration between 1.9% and 3.7% it is possible to decrease the metabolism of these seeds. In addition, a model that allows controlling the factors involved in the analysis of respiratory rates in seeds is presented.